2003
DOI: 10.1891/0047-2220.34.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury and Rehabilitation Outcomes: Does the Working Alliance Make a Difference?

Abstract: This study investigated the impact of the working alliance on vocational rehabilitation outcomes for individuals with traumatic brain injury. The working alliance is defined as collaboration between the client and counselor supported by the development of an attachment bond as well as a shared commitment to the goals and tasks of counseling. Research supports the relationship between the working alliance and positive counseling outcomes. This study extends previous research and considers the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Furthermore, the influence of treatment expectancy upon self-ratings prior to treatment warrants further consideration [39]. The assessment environment, specifically the therapeutic alliance, has been found to be positively related to outcomes in therapy for individuals with brain injury [46]. This finding highlights the potential for the alliance between the therapist and client during the COPM interview to influence the number and nature of problems identified on the COPM.…”
Section: Clinical Implications and Methodological Considerationsmentioning
confidence: 99%
“…Furthermore, the influence of treatment expectancy upon self-ratings prior to treatment warrants further consideration [39]. The assessment environment, specifically the therapeutic alliance, has been found to be positively related to outcomes in therapy for individuals with brain injury [46]. This finding highlights the potential for the alliance between the therapist and client during the COPM interview to influence the number and nature of problems identified on the COPM.…”
Section: Clinical Implications and Methodological Considerationsmentioning
confidence: 99%
“…A review of articles related to the topic of brain injury published in rehabilitation counselling journals in the last 20 years shows a primary focus on the experience of the individual with a TBI (e.g., Fabiano, Crewe, & Goran, 1995;Gamble & Satcher, 2002;Garske & Thomas, 1992;Hallauer, Prosser, & Swift, 1989;Kaplan, 1990;Lam, Priddy, & Johnson, 1991;Lustig, Strauser, Weems, Donnell, & Smith, 2003;Marme' & Skord, 1993;Michaels & Risucci, 1993;Moore & Bartlow, 1990;Preston, Ulicny, & Evans, 1992;Schonbrun & Kampfe, 2004), and relatively little on the experience of family members and caregivers. The limited body of extant research on families has mostly focused on postinjury adaptation and coping (e.g., Degeneffe & Lynch, 2006;Kosciulek, 1994Kosciulek, , 1996Kosciulek & Lustig, 1998;Kosciulek, McCubbin, & McCubbin, 1993).…”
mentioning
confidence: 99%
“…Th e working alliance provides the foundation for the counseling approach to evaluation wherein the emphasis is on building a solid relationship with the individual, developing realistic and obtainable goals, and determining what tasks lead to goal accomplishment Strauser et al, 2014). Considerable evidence has found that a well-developed working alliance leads to better rehabilitation outcomes for persons with disabilities (Chan, Shaw, McMahon, Koch, & Strauser, 1997;Lustig, Strauser, Weems, Donnell, & Smith, 2003;Strauser et al, 2014). When assessment is approached with the working alliance as a foundation, the focus should fi rst be directed at developing a relationship with the individual that will contribute to accomplishing eff ective goals and tasks.…”
Section: Advantages and Meritsmentioning
confidence: 99%